Determination of Aflatoxin B1 Contamination of Commercial Mixed Feeds (For Dairy Cow) by Immunoaffinity Column Using High Performance Liquid Chromatography - KOC, FISUN; SUNNETCI, SELIM; COSKUNTUNA, ARZU; COSKUNTUNA, LEVENT (Asian Journal of Chemistry, 2010)
In this study, aflatoxin B1 levels of commercial mixed feeds (for dairy cow) produced in Thrace region, Turkey were determined by immunoaffinity column and HPLC and the results were compared with the values accepted by Turkish Feed Legislation. Aflatoxin B1 levels of 104 feed samples collected from 8 factories in 2 different seasons (June- July-August; December-January-February) ranged between 0 to 7.83 μg kg. Two samples (5.19 and 7.83 μg kg) had exceeded the tolerance limit accepted by Turkish Feed Legislation (5 μg kg). It was also recorded for samples collected in the second season (December-January-February) from the point of seasonal variation. It was noted that aflatoxin B1 content of the samples collected in the winter. Seasonal variations with regard to aflatoxin B1 were statistically significant (p < 0.01). As a result, aflatoxin B1 levels in 98.07 % of the samples provided throughout the year did not exceed the maximum tolerance limit established by Turkish Feed Legislation.